Managing quality - edited by Barrie G. Dale; David Bamford and Ton van der Wiele (Wiley, 2016)
This popular and highly successful text on Quality Management has been fully revised and updated to reflect recent developments in the field. New to the Sixth Edition is timely coverage of agile development, emerging markets, product research, evidence based decision-making, and quality control. Some of the material has been re-ordered and changes to terminology have been made to bring the book completely up to date. Contributions from new co-author David Bamford offer insights from a veteran teacher and practitioner